MYSTERIOUS EmoGate - Savina A/P A.Saiman; Aina Fauziaa Ahmad Shafian; Nor Husna Mohd Tambyzy; Nursabirah Ainaa Burhanuddin (Malaysia Journal of Invention and Innovation, 2024)
In today’s day and age, students face problems in structuring sentences appropriately, using low  frequency words in their essays due to various factors. They have negative perceptions towards learning new vocabulary, and to make it worse, they feel afraid to explore new words. In this endeavor, they are only proficient at B1 and B2 levels, and they do not know how to distinguish words with similar spellings or pronunciations while reading or speaking. Thus, this game is aligned to meet the purpose and aim of making students learn low-frequency words effectively and much more easily. Needless to say, by playing this game, students can memorize low-frequency words, including their meanings and CEFR levels, as they gradually play the game. The impact of this innovation is that students were able to obtain C1 and C2 levels for reading. Apart from that, we have spread the use of our Mysterious EmoGate game to other students at our school and other schools, parents, and so on through links,QR codes, YouTube, and Telegram.